Ethnography at a Crossroads: Care Economy and Forms of Otherness/ Identity in a Middle Class Neighborhood - Acha Kutscher, Elisabeth Juana (2023)
From an ethnographic perspective, through the life histories of different actors—neighbors, caretakers and people who provide different services on the streets,—and also participant observation in parks and main shopping center, neighborhood’s events and WhatsApp groups, our aim is to identify the affective practices that sustain the care economy, and what it means for caretakers to look after the most intimate and vital aspects of another family from a different social class on a daily basis in order to achieve a peaceful life. This is also valid for the people taking care of streets and parks. These practices reveal ways of interacting and relating to othersand making sense of it. These dynamics reveal encounters, conflicts, negotiations, and borders that reproduce the symbolic fabric that composes the social space between the inside of different social sectors of residents and non-residents, besides securing care and the politics of care. In the sameway that pedestrians make the city, caretakers and people who provide services make the reproduction of a middle-class neighborhood possible.